Harbours as unique environmental sites of multiple anthropogenic stressors on fish hormonal systems. (15th September 2022) - Gairin, Emma; Dussenne, Mélanie; Mercader, Manon; Berthe, Cécile; Reynaud, Mathieu; Metian, Marc; Mills, Suzanne C.; Lenfant, Philippe; Besseau, Laurence; Bertucci, Frédéric; Lecchini, David
Abstract: Fish development and acclimation to environmental conditions are strongly mediated by the hormonal endocrine system. In environments contaminated by anthropogenic stressors, hormonal pathway alterations can be detrimental for growth, survival, fitness, and at a larger scale for population maintenance. In the context of increasingly contaminated marine environments worldwide, numerous laboratory studies have confirmed the effect of one or a combination of pollutants on fish hormonal systems. However, this has not been confirmed in situ . In this review, we explore the body of knowledge related to the influence of anthropogenic stressors disrupting fish endocrine systems, recent advances (focusing on thyroid hormones and stress hormones such as cortisol), and potential research perspectives. Through this review, we highlight how harbours can be used as " in situ laboratories" given the variety of anthropogenic stressors (such as plastic, chemical, sound, light pollution, and invasive species) that can be simultaneously investigated in harbours over long periods of time.